2004
DOI: 10.1002/zaac.200400383
|View full text |Cite
|
Sign up to set email alerts
|

Kristallstrukturen und spektroskopische Eigenschaften von 2λ3‐Phospha‐1, 3‐dionaten und 1, 3‐Dionaten des Calciums ‐ ein Vergleich am Beispiel der 1, 3‐Diphenyl‐ und 1, 3‐Di(tert‐butyl)‐Derivate

Abstract: Der Wasserstoff‐Metall‐Austausch zwischen Dibenzoylphosphan und Calciumcarbid in Tetrahydrofuran (THF) ergibt nach Zusatz des Liganden 1, 3, 5‐Trimethyl‐1, 3, 5‐triazinan (TMTA) den als Kokristallisat mit Benzol isolierten zweikernigen Komplex Bis[(tmta‐N, N′, N″)calcium‐bis(dibenzoylphosphanid)] (1a). In ähnlicher Weise führt die Umsetzung von Bis(2, 2‐dimethylpropionyl)phosphan mit Bis(thf‐O)calcium‐bis[bis(trimethylsilyl)amid] in 1, 2‐Dimethoxyethan (DME) mit guten Ausbeuten zum ‐Bis(dme‐O, O′)calcium‐bis[b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
15
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(15 citation statements)
references
References 77 publications
0
15
0
Order By: Relevance
“…The corresponding 31 P{ 1 H} and 31 PNMR signals were found to be triplets at d = 35.3 ppm, indicating the incorporation of two equivalents of 13 CO.R epeating the reaction of [ 13 C]2 with unlabeled CO afforded an analogous doublet ( 1 J P-C = 97 Hz) 31 Ps ignal with ac hemical shift of d = 35.4 ppm. The[(OCtBu) 2 P] À ligand was found to be planar with average PÀCa nd CÀOb ond distances of 1.812(2) and 1.234(2) , respectively,a nd aC ÀPÀCa ngle of 105.28 8.T his fragment is bound to the potassium ion by KÀOb onds that were determined to be 2.729(1) and 2.689(1) .The KÀOdistances to the crown-ether fragment in 5 were found to average 2.902 .I ti sn oteworthy that the groups of Becker [15] and Grützmacher [16] have previously reported related diacyl-phosphides.B ecker and colleagues described various metal salts of related anionic ligands [17] and Goicocechea and coworkers have described related bis(carbamoyl) phosphides. 5 was crystallized from aT HF/pentane solution and the X-ray study confirmed the above formulation as the Ks alt of the diacyl-phosphide anion ( Figure 5).…”
Section: Angewandte Chemiementioning
confidence: 99%
See 1 more Smart Citation
“…The corresponding 31 P{ 1 H} and 31 PNMR signals were found to be triplets at d = 35.3 ppm, indicating the incorporation of two equivalents of 13 CO.R epeating the reaction of [ 13 C]2 with unlabeled CO afforded an analogous doublet ( 1 J P-C = 97 Hz) 31 Ps ignal with ac hemical shift of d = 35.4 ppm. The[(OCtBu) 2 P] À ligand was found to be planar with average PÀCa nd CÀOb ond distances of 1.812(2) and 1.234(2) , respectively,a nd aC ÀPÀCa ngle of 105.28 8.T his fragment is bound to the potassium ion by KÀOb onds that were determined to be 2.729(1) and 2.689(1) .The KÀOdistances to the crown-ether fragment in 5 were found to average 2.902 .I ti sn oteworthy that the groups of Becker [15] and Grützmacher [16] have previously reported related diacyl-phosphides.B ecker and colleagues described various metal salts of related anionic ligands [17] and Goicocechea and coworkers have described related bis(carbamoyl) phosphides. 5 was crystallized from aT HF/pentane solution and the X-ray study confirmed the above formulation as the Ks alt of the diacyl-phosphide anion ( Figure 5).…”
Section: Angewandte Chemiementioning
confidence: 99%
“…5 was crystallized from aT HF/pentane solution and the X-ray study confirmed the above formulation as the Ks alt of the diacyl-phosphide anion ( Figure 5). The[(OCtBu) 2 P] À ligand was found to be planar with average PÀCa nd CÀOb ond distances of 1.812(2) and 1.234(2) , respectively,a nd aC ÀPÀCa ngle of 105.28 8.T his fragment is bound to the potassium ion by KÀOb onds that were determined to be 2.729(1) and 2.689(1) .The KÀOdistances to the crown-ether fragment in 5 were found to average 2.902 .I ti sn oteworthy that the groups of Becker [15] and Grützmacher [16] have previously reported related diacyl-phosphides.B ecker and colleagues described various metal salts of related anionic ligands [17] and Goicocechea and coworkers have described related bis(carbamoyl) phosphides. [18] In considering the mechanism of formation of 2 and 5,i t was noted that the formation of these products from the reactions of 1 and 2,r espectively,w ith CO suggest intermediates with carbene character.T he subsequent 1,2 migration of the tBu group from phosphorus to the adjacent carbon center, affording 2,isthe dominant pathway.Interestingly and in contrast, Grützmacher et al [14] observed 1,2-hydrogen atom migration in the reaction of NaPH 2 with CO,a ffording [HPCHO] as aminor byproduct, while the major product was Na [PCO].D imerization of the carbene affords [(tBu 2 PCO) 2 ] 2À ,which oligomerizes to give 3.Itisnoteworthy that this alkyl migration that yields 2 is analogous to those reported by Bertrand et al, [19] where rearrangements of acyclicc arbenes of the form R 2 PCR' (R = tBu, R' = Me or tBu) occurred above À10 8 8C.…”
Section: Angewandte Chemiementioning
confidence: 99%
“…As expected, the shortened P À C bonds (1.77-1.80 ) and elongated C À O bonds (1.25-1.26 ) indicate significant p-conjugation and charge delocalization over the O-C-P-C-O p-system. [22] Compound 2 is remarkably stable to hydrolysis and can be dissolved in solvents containing water. In the solid state it can be briefly handled in air.…”
Section: Angewandte Zuschriftenmentioning
confidence: 99%
“…[19] The reported synthetic routes requiring a primary phosphane (RPH 2 ) or a metallated derivative (RPH 2Àx M x ) are incompatible with many functional groups and only aryl or alkyl substituents are bound to the phosphorus atom. [22] Compound 2 is remarkably stable to hydrolysis and can be dissolved in solvents containing water. NaPH 2 is easily obtained from elemental phosphorus, sodium, and tert-butanol in the form of a sodium tert-butylate aggregate, which is a versatile starting material for functional phosphorus compounds.…”
mentioning
confidence: 99%
“…The general Ca-O distances for seven coordinated calcium compounds are between 2.37 Å and 2.82 Å. [28,42,43] Compound 3 has a mean Ca-O distance (average of all Ca-O bonds) of 2.374 Å. This is due to the stronger electron attraction of the calcium ion and a tight bonding of the ligand.…”
Section: Comparison Of Calcium Compoundsmentioning
confidence: 99%